Assessment of trace element toxicity in surface water of a fish breeding river in Bangladesh: a novel approach for ecological and health risk evaluation. (3rd April 2022) - Rakib, Md. Refat Jahan; Jolly, Yeasmin Nahar; Begum, Bilkis Ara; Choudhury, Tasrina Rabia; Fatema, Konika Jannat; Islam, Md. Saiful; Ali, Mir Mohammad; Idris, Abubakr M.
Abstract: In recent decades, water quality is a great concern for the human being as it is the most important natural resource but water is polluted by increasing population activities. In this study, surface water samples were collected in the wet and the dry season from Halda River, Bangladesh, and 12 physicochemical properties and 10 traces elements (Cd, Cr, Mn, Fe, Co, Cu, Zn, As, Pb, and Hg) were analyzed to assess the metal toxicity, identify the possible sources, and determine possible carcinogenic and noncarcinogenic risk for adults and child residents. During wet season, the mean concentrations of Cd, Cr, Mn, Fe, Co, Cu, Zn, As, Pb, and Hg were 0.032 ± 0.028, 0.004 ± 0.002, 0.010 ± 0.012, 0.38 ± 0.08, 0.010 ± 0.017, 3.33 ± 1.16, 0.062 ± 0.008, 1.34 ± 1.17, 0.030 ± 0.014, and 0.007 ± 0.002 mg/L, respectively, whereas the concentrations were measured as 0.04 ± 0.017, 0.060 ± 0.036, 0.150 ± 0.134, 0.58 ± 0.11, 0.049 ± 0.017, 0.172 ± 0.166, 0.393 ± 0.212, 1.07 ± 0.989, 0.104 ± 0.121, and 0.003 ± 0.002 mg/L, respectively, during the dry season. The levels of trace elements in water samples were much higher than the guideline values for safe limits of drinking water and the protection of freshwater aquatic life, indicated that water from this river is not safe for drinking and/or cooking purposes. Trace element evaluation index indicated that water was found to be high contamination while ecological risk index showed low to very high contamination. All hazard quotient and hazard index (HI) values were higher than the risk threshold of unity. HI values for child were higher than those for adult, indicating that the health of children is at dramatically higher risk than adults. Arsenic for water ingestion and dermal pathways was the primary contributors to total health risk (HI/THI) indicated that As in surface water of the Halda River might pose health risks to residential users.